The Role and Value of Out-of-School Environments in Science Education for 21st Century Skills - Berg, Thomas Bjørneboe; Achiam, Marianne; Poulsen, Kristian Mandrup; Sanderhoff, Lene Bech; Tøttrup, Anders P. (Frontiers in Education, 2021)
The global ‘wicked’ problems we face in the 21st century call for 21st century competencies. The formal education system is hard pressed to foster these competencies within the science curriculum. Accordingly, we argue that out-of-school science education can function as an alternative pathway to 21st century competencies among learners. We present four distinct community case stories on teaching science in out-of-school environments and link them to a number of key challenges linked to achieving 21st century competencies. Natural history museums have been the foundation of science for four centuries and have served as the basis upon which nomenclature of all living species and the concept of evolution has been developed, hence our first case takes place within this frame. Without fieldwork natural history museums would not have any collections and Case 2 takes us out there where it all begins. Humans affect the entire globe and all living matters. Case 3 tells the story of how waste becomes authentic and debatable during a visit to a wastewater plant. Finally, new technologies in the service of natural science is the scope for Case 4 where students collect and analyze their samples of eDNA at university lab facilities in collaboration with scientists, generating valuable real data for research projects. We summarize by discussing how, to meet the challenges of the future, there is a need to strengthen the content and context of curriculums as well as the skills of the learners within natural sciences. The four cases address different themes and skills connected to the highly complex problems like climate change and loss of biodiversity, that may be difficult to comprehend for the greater public but are urgent to teach the adults of tomorrow.